Assessing cognitive function in longitudinal studies of ageing worldwide: some practical considerations. - Feeney, Joanne; Kenny, Rose (My University, 2023)
Over 55 million people live with dementia worldwide. With 40% of modifiable risk factors estimated to contribute to dementia, the potential for prevention is high, and preventive measures, at an early stage of cognitive decline, are likely to positively influence future dementia trends. Countries need reliable health data and adequate measurement tools to quantify, monitor and track early changes in cognitive capacity in the general population. Many cognitive tests exist; however, there is no consensus to date about which instruments should be employed, and important variations in measurement have been observed. In this narrative review, we present a number of cognitive tests that have been used in nationally representative population-based longitudinal studies of ageing. Longitudinal panel studies of ageing represent critical platforms towards capturing the process of cognitive ageing and understanding associated risk and protective factors. We highlight optimal measures for use at a population level and for cross-country comparisons, taking into consideration instrument reliability, validity, duration, ease of administration, costs, literacy and numeracy requirements, adaptability to sensory and fine motor impairments and portability to different cultural and linguistic milieux. Drawing upon the strengths and limitations of each of these tests, and the experience gained and lessons learnt from conducting a nationally representative study of ageing, we indicate a comprehensive battery of tests for the assessment of cognitive capacity, designed to facilitate its standardised operationalisation worldwide.
PUBLISHED
Keywords: ageing, cognitive capacity, cross-countries comparison, early detection, longitudinal studies, older people; Ageing